Reconsideration of histopathology and ultrastructural aspects of the human liver in yellow fever - Quaresma, JAS; Barros, VLRS; Fernandes, E. R.; Pagliari, C.; Takakura, C.; Vasconcelos, PFD; Andrade, H. F. de; Duarte, MIS (Elsevier B.V., 2005)
Yellow fever is a re-emerging infectious disease that currently is at risk of urbanization due to the advance of the Aedes aegypti vector. The disease affects about 200,000 individuals annually, mainly in tropical Africa and South America. It causes severe disease involving especially the liver, with lesions characterized by midzonal steatosis, apoptosis and lytic necrosis of the hepatocytes. Quantitative histological and immunohistochemical analysis of 53 human hepatic samples demonstrated apoptosis, steatosis and lytic necrosis of hepatocytes with midzonal pattern. No substantial alterations and reticular network were observed. The inflammatory infiltrate consisted of mononuclear cells and intensity was minimal or moderate, disproportionate to the intense death of the hepatocytes. Hepatic damage in yellow fever resulted mainly from a massive death of hepatocytes due to apoptosis and to a lesser extent due to lytic necrosis. It is recommended that therapeutic regimens for serious cases should include measures to protect against apoptosis. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: yellow fever; histopathology; apoptosis; necrosis; steatosis